1973
DOI: 10.1107/s0021889873008587
|View full text |Cite
|
Sign up to set email alerts
|

Powder diffraction data for U3O5P2O7

Abstract: X‐ray powder diffraction data have been obtained for U3O5P2O7. This compound has not yet been mentioned in the literature, although similar diffraction data have been reported for a compound described as (UO)3(PO4)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…It was, however, observed that the X-ray diffraction pattern of the crystalline sample of U3OsP~O7 [19], described above, was nearly identical with that for (UO)z(PO4)2 reported by Burdese and Borlera. It is therefore not impossible that their product was actually UaQP2OT, which might have been formed by oxidation of the mixture [UOz + (UO)2P~OT] by traces of oxygen in the inert gas they used.…”
Section: Reduction Of Nupt With Carbon Black In Argonsupporting
confidence: 82%
“…It was, however, observed that the X-ray diffraction pattern of the crystalline sample of U3OsP~O7 [19], described above, was nearly identical with that for (UO)z(PO4)2 reported by Burdese and Borlera. It is therefore not impossible that their product was actually UaQP2OT, which might have been formed by oxidation of the mixture [UOz + (UO)2P~OT] by traces of oxygen in the inert gas they used.…”
Section: Reduction Of Nupt With Carbon Black In Argonsupporting
confidence: 82%
“…In this study, the synthesis of cerium (IV) phosphatehydrogenphosphate hydrate was undertaken in the same conditions as UPHPH using (NH 4 ) 2 Ce(NO 3 ) 6 and H 3 PO 4 solutions. For this sample, the EPMA results are given in Table 1 while the SEM micrographs are presented in Fig.…”
Section: Cerium Phosphate-hydrogenphosphate Hydratementioning
confidence: 99%
“…Tetravalent uranium phosphates were extensively studied in the past [1][2][3][4][5][6][7][8][9][10][11]. However, their chemistry required to be revised since the general physico-chemical properties of these solids (and especially their low solubility) appear of particular interest for their potential use as conditioning matrices for radioactive waste.…”
Section: Introductionmentioning
confidence: 99%
“…In an article by Schaekers & Greybe (1973) a powder pattern from U305P207 is given and compared with a pattern from a compound (UO)3(PO4)2 published in the paper by Burdese & Borlera (1963) discussed above. Schaekers & Greybe claim that the two powder patterns arise from the same compound, U3OsP2Ov.…”
Section: Examples*mentioning
confidence: 99%